The Research on Dynamic Changes of Fracture Width in Fractured/Caved Carbonate Reservoirs - Daqi, Li; Yili, Kang (Physical and Numerical Simulation of Geotechnical Engineering, 2017)
To predict the dynamic width of the fracture during drilling in fractured/caved carbonate reservoirs, the physical model and finite element model of mud losses have been established, based on the condition of fractures or caves and the mechanisms of lost circulation. How fracture length, cave diameter, overbalance pressure differential and leakoff time effecting fracture width changes are investigated. The results show that the dynamics fracture width increases with the increase of overbalance differential pressure, cave diameter, fracture length and leakoff time, among which the overbalance pressure differential and cave diameter are the most important factors. Fracture has "flat, straight and wide" features in high differential pressure, large diameter, short fracture length, and long leakoff time. This increases the difficulty of lost circulation prevention and control and the difficulty of reservoirs protection. Therefore, the lost circulation prevention should be put in the first place, and plugging measures should be executed timely, promptly and efficiently.